Ispol'zovanie lyžnogo tonnelja v trenirovke lyžnikov-gonšcikov vysokoj kvalifikacii v bessnežnoe vremja goda - Onuchin, L. A. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to analyze benefits of the ski tunnel practices in the snowless season for elite cross-country skiers, and to provide theoretical grounds for its practical application in training systems applied by Class I Athletes, Masters of Sports and World Class Athletes. Reference Groups (RG) were trained as required by the traditional annual training system, whilst the Experimental Group (EG) training was designed to include a few ski tunnel micro-cycles in the snowless season. A significant increase in athletic technical results at the beginning of the competitive period indicates the effectiveness of the developed special physical training method for elite cross-country skiers with the use of ski tunnel. The training model was found beneficial as verified by the significant progress of the EG versus the RG in the physical and technical aspects prior to the competitive period. The study data and analyses show benefits of the special physical training micro-cycles including the ski tunnel practices in the snowless season for the skilled cross-country skiers to keep up their physical fitness and motor skills.